Sistem Monitoring Kondisi Kendaraan Motor Injeksi Berbasis Mikrokontroler - Nurus Sholeh; Koko Joni; Miftachul Ulum (Universitas Darul Ulum, 2020)
The use of motorbikes in indonesia is very suitable for the needs of the community because the price is relatively cheap, affordable for most people and the use of fuel and operational costs are quite economical. But sometimes vehicle owners forget not to pay attention to the condition of the motorbike because of their busy activities, so that the motorcycle breaks down on the engine parts. Based on these problems, a microcontroller-based system was made which gave a warning to the owners of voxion motorcycle vehicles. Microcontroller is a computer system that all or most of its elements are packaged in one ic chip, so it is often called a single chip microcomputer. Where this system prioritizes timeliness in oil changes, radiator water and indicators of damage in motorbikes. Submission of oil information using the buzzer. Radiators and indicators of damage to motorbikes are done via sms gateway to smart phones or android. For that we need data that is input into a system to be read by the tool. The tools used for monitoring motor conditions include speed sensors, arduino, at mega 8535, buzzer and sms gateway.